An interesting case of tuberculosis of the thyroid gland - C., Tharun Ganapathy; Suresh, Abinayaah; Sekhar, Sidhu (International Surgery Journal, 2019)
Tuberculosis has been reported in many parts of the human body but thyroid gland involvement is extremely rare and its true incidence is still unknown. Tuberculosis of the thyroid is a rare entity even in countries where tuberculosis is prevalent as an endemic problem. Tuberculosis of thyroid gland can present as cold abscess, multinodular goitre, acute abscess or generalized goitre. Clinically, these patients can be euthyroid, hypothyroid or hyperthyroid. Here we report an unusual presentation of recurrent neck swelling in an 8 year old girl turning out to be tuberculosis of thyroid gland.